The Influence of Job Insecurity and Organizational Support on Turnover Intention of Non-PNS Employees at Sriwijaya University in the Context of Status Change from BLU to PTN-BH - Syuryani, Devita; Sulastri, Sulastri; Hadjri, Muhammad Ichsan; Adam, Mohamad (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study was conducted with the aim of determining the effect of job insecurity and organizational support on turnover intention of non-PNS employees at Sriwijaya University in the context of changing the status of BLU to PTN-BH. In this study, the population was all Non-PNS Education Personnel at Sriwijaya University totaling 772 people.The sample of this study used a probability sampling technique, namely proportionate stratified random sampling. The number of samples used was based on the sampling formula using the Slovin formula, so the number of samples used was 264 samples. The results of the multiple linear regression analysis showed that job insecurity and organizational support had a positive and significant effect on turnover intention. Job insecurity is expected to provide clarity on how the clarity and status of non-PNS employees in the Sriwijaya University environment for the long term. Organizational support is expected to provide training and opportunities for employees to be able to develop skills that can support their work.